A phase I clinical study to evaluate safety of orally administered, genetically engineered Salmonella enterica serovar Typhimurium for canine osteosarcoma. Issue 3 (6th June 2016) - Fritz, Sara E.; Henson, Michael S.; Greengard, Emily; Winter, Amber L.; Stuebner, Kathleen M.; Yoon, Una; Wilk, Vicki L.; Borgatti, Antonella; Augustin, Lance B.; Modiano, Jaime F.; Saltzman, Daniel A.
Abstract: We conducted a prospective phase I study to evaluate safety of an orally administered Salmonella encoding IL‐2 (SalpIL2) in combination with amputation and adjuvant doxorubicin for canine appendicular osteosarcoma. Efficacy was assessed as a secondary measure. The first dose of SalpIL2 was administered to 19 dogs on Day 0; amputation was done after 10 days with chemotherapy following 2 weeks later. SalpIL2 was administered concurrent with chemotherapy, for a total of five doses of doxorubicin and six doses of SalpIL2. There were six reportable events prior to chemotherapy, but none appeared due to SalpIL2. Dogs receiving SalpIL2 had significantly longer disease‐free interval (DFI) than a comparison group of dogs treated with doxorubicin alone. Dogs treated using lower doses of SalpIL2 also had longer DFI than dogs treated using the highest SalpIL2 dose. The data indicate that SalpIL2 is safe and well tolerated, which supports additional testing to establish the potential for SalpIL2 as a novel form of adjuvant therapy for dogs with osteosarcoma. Abstract : We conducted a prospective phase I study to evaluate safety of an orally administered Salmonella encoding IL‐2 (SalpIL2) in combination with amputation and adjuvant doxorubicin for canine appendicular osteosarcoma. Dogs receiving SalpIL2 had significantly longer disease‐free interval (DFI) than a comparison group of dogs treated with doxorubicin alone.